Book Review: Faithful Generations: Effective Ministry across Generational Lines - Merensiana Hale (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
The diversity of spirituality patterns of generations in the church is a reality. Each generation has a unique style of spirituality. This uniqueness is a gift from God which of course is also shaped by the life experiences of each generation that is permitted by God. This challenges the church to carry out a generation-based ministry to develop the spirituality of the congregation. This paper helps ministers to understand the spiritual characteristics of each generation as a basis for developing intergenerational spirituality ministries. The uniqueness of the spirituality of generations must be embraced in the fellowship of the congregation as the family of God.